Executive Compensation and Horizon Incentives: an Empirical Investigation - HUANG, Sheng (Institutional Knowledge at Singapore Management University, 2012)
This paper investigates the hypothesis that CEOs in their final years of office manage discretionary investment expenditures to improve short-term earnings performance. We examine the behavior of R & D expenditures for a sample of firms in industries that have significant ongoing R & D activities. The results suggest that CEOs spend less on R & D during their final years in office. However, we find the reductions in R & D expenditures are mitigated through CEO stock ownership. There is no evidence that the reduced R & D expenditures are associated with either poor firm performance or reductions in investment expenditures that are capitalized for accounting purposes.